Adsorption of atomic hydrogen on defect sites of graphite: Influence of surface reconstruction and irradiation damage. (February 2018) - Lechner, Christoph; Baranek, Philippe; Vach, Holger
Abstract: The influence of surface reconstruction and defects due to irradiation damage on the trapping of hydrogen in nuclear graphite has been investigated at the ab initio level. Several models of defects and surfaces have been studied and compared with previously proposed traps, i.e. the zig zag edge of dislocation loops and reconstructed surfaces of graphite crystallites. The relative stabilities of hydrogen adsorption on the (100), (110), and (001) graphite basic planes have been evaluated for different amounts of hydrogen coverage and various types of reconstruction. The unreconstructed (100) surface adsorbs hydrogen the strongest. The (100) and (110) surface reconstructions result in a decreased stability for H adsorption compared to unrelaxed surfaces. Point defects caused by irradiation, such as mono- and divacancies, also trap hydrogen. We find that extended defects are weaker traps than monovacancies. This is true for surface defects as well as for bulk defects. The obtained results show that the existing hypothesis for trapping at dislocation loops has to be refined. Finally, an agreement with experiments is obtained for trapping on the reconstructed surfaces. Graphical abstract: Image 1